Gerakan Misi Kaum Awam dan Terbentuknya Komunitas Peranakan Kristen di Jawa Barat 1858-1889 - Firdaus, Yogi Fitra (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2023)
The lay missionary movement became characteristic of the Chinese Peranakan identity and community in West Java in the mid-19th century. Lay evangelists played a major role in the formation of Christian Peranakan communities in Indramayu, Cirebon, Batavia, and Bandung. Peranakan communities were formed long before the Dutch mission agency paid attention to the Chinese community. While it is true that pioneers of the Christian Peranakan community first heard the gospel message from Dutch pastors, it does not mean that Chinese churches in West Java were merely a zending heritage. Peranakan lay people were actively spreading the gospel through Bible study groups, discipleship, and their involvement in social issues. Unfortunately, stories that feature lay missionary achievements are often lost in the historical narratives of the church in Indonesia that are written mostly by Dutch historians. Such a lacuna has led to the loss of identity and missional vocation of the lay Chinese Christians as if they were never part of the mission and church history in Indonesia. This article thus attempts to historically examine and rebuild the narrative of the participation of the Chinese laity and see the factors that contribute to the weakening of the lay missionary spirit and their involvement among the Chinese church in West Java today. It is hoped that Chinese churches can once again sense the urgency to resurrect the lay missionary movement in the present age.